2013
DOI: 10.1155/2013/258517
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections due to Multidrug-Resistant Enterobacteriaceae: Prevalence and Risk Factors in a Chicago Emergency Department

Abstract: Background. Selection of empiric antibiotics for urinary tract infections (UTIs) has become more challenging because of the increasing rates of multidrug-resistant Enterobacteriaceae (MDRE) infections. Methods. This retrospective study was conducted to determine antibiotic resistance patterns, risk factors, and appropriate empiric antibiotic selection for MDRE UTIs. Adult patients seen in the Emergency Department (ED) with Enterobacteriaceae UTIs during 2008-2009 were identified from review of microbiology rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
95
5
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 24 publications
11
95
5
6
Order By: Relevance
“…Specifically, it showed that high prevalence of MDR E. coli isolates identified from patients with UTI was 92.9% (95% confidence interval: 87.3%-97.7%). The rate of MDR E. coli demonstrated in this study was much higher than findings from developed countries [8][9][10], but comparable to published data from low income countries [4,5,11,12]. However, few reports from developing countries documented lower prevalence of MDR E. coli as compared to this study [13][14][15][16].…”
Section: Discussionsupporting
confidence: 79%
“…Specifically, it showed that high prevalence of MDR E. coli isolates identified from patients with UTI was 92.9% (95% confidence interval: 87.3%-97.7%). The rate of MDR E. coli demonstrated in this study was much higher than findings from developed countries [8][9][10], but comparable to published data from low income countries [4,5,11,12]. However, few reports from developing countries documented lower prevalence of MDR E. coli as compared to this study [13][14][15][16].…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies have demonstrated that use of antimicrobials in the 4 weeks to 1 year preceding the index infection increases the probability of MDR in the index infection. Use of fluoroquinolones and antipseudomonal penicillins, as well as more cumulative days of treatment with any antimicrobial prior to UTI presentation, were most strongly associated with resistance [3,11,12].…”
Section: Risk Factors For Utis Caused By Mdr Uropathogensmentioning
confidence: 99%
“…Men who present with acute cystitis in the outpatient setting may have an uncomplicated infection, though predisposing anatomical and functional risk factors for infection should be considered, particularly related to the prostate. The likelihood of resistance can be higher among men, and a urine culture is warranted to help adjust whatever empiric therapy is chosen and to help inform management of future infections [3]. Any patient (regardless of sex) considered to be at risk of having a UTI due to a multidrug-resistant (MDR) uropathogen (generally considered nonsusceptible to ≥1 agent in ≥3 antibiotic classes, though definitions may vary by institution) should have a urine culture performed as part of the initial assessment in order to tailor the empiric therapy and inform empiric antimicrobial selection in the case of future occurrences [4].…”
mentioning
confidence: 99%
“…As urinary sources are one of the most common sources of bacteremia caused by Gram-negative bacteria and treatment for UTIs is usually initiated prior to the availability of microbiologic data, it is important to optimize decision making for the initial choice of antimicrobial therapy. Although previous studies have examined the rates of inaccurate therapy for MDR UTIs, few have evaluated strategies for improving accuracy (9)(10)(11).…”
mentioning
confidence: 99%